Effect of Sulphide on Admiralty Brass in Seawater - PILLAI, A. G. GOPALAKRISHNA; RAVINDRAN, K. (Fishery Technology, 2017)
The corrosion behaviour of admiralty brass in putrifi.ed seawater has been studied. It was observed that when the dissolved oxygen in the putrifi.ed seawater medium hasÂ attained very low value ( < 0.53 p.p.m) the corrosion rate of admiralty brass showed decreasing trend inspite of increased level of sulphide from 21.2 to 228 p.p.m. Significant correlations (negative) were observed between corrosion rates and log period of exposure.